2020
DOI: 10.1021/acs.est.0c07243
|View full text |Cite
|
Sign up to set email alerts
|

Dust-Dominated Coarse Particles as a Medium for Rapid Secondary Organic and Inorganic Aerosol Formation in Highly Polluted Air

Abstract: Secondary aerosol (SA) frequently drives severe haze formation on the North China Plain. However, previous studies mostly focused on submicron SA formation, thus our understanding of SA formation on supermicron particles remains poor. In this study, PM2.5 chemical composition and PM10 number size distribution measurements revealed that the SA formation occurred in very distinct size ranges. In particular, SA formation on dust-dominated supermicron particles was surprisingly high and increased with relative hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 82 publications
0
31
1
Order By: Relevance
“…The possible inter-particle interaction between fine and coarse particles on the PM10 samples is also neglected, which potentially bias the nitrate measurements in the two size modes. secondary inorganic and organic aerosols formation in highly polluted condition (Xu et al, 2020). Considering the southern China is more humid than northern China, our study region presents an atmospheric condition different from that in Xu et al's study, which is more favourable to adsorption of water on mineral dust, and consequently lead to different impacts on atmospheric chemistry and climate (Tang et al, 2016).…”
Section: Implications To Atmospheric Research and Public Healthmentioning
confidence: 76%
See 1 more Smart Citation
“…The possible inter-particle interaction between fine and coarse particles on the PM10 samples is also neglected, which potentially bias the nitrate measurements in the two size modes. secondary inorganic and organic aerosols formation in highly polluted condition (Xu et al, 2020). Considering the southern China is more humid than northern China, our study region presents an atmospheric condition different from that in Xu et al's study, which is more favourable to adsorption of water on mineral dust, and consequently lead to different impacts on atmospheric chemistry and climate (Tang et al, 2016).…”
Section: Implications To Atmospheric Research and Public Healthmentioning
confidence: 76%
“…For example, nitrate in the coarse mode is formed by the reaction between nitric acid (HNO3) from oxidation of NOx and preexisting alkaline aerosols (e.g., sea salt and dust). A recent study showed that mineral dust can serve as a medium for rapid secondary inorganic and organic aerosol formation under high photochemical activity and relative humidity conditions, which has important implications to the life cycle of secondary aerosols (Xu et al, 2020). PMcoarse also exerts an impact on earth's climate because of its continuous loading in the atmosphere and its ability to scatter and absorb radiation or act as cloud condensation and ice nuclei (USEPA, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary aerosol formation is enhanced in stagnant (low winds) and high humidity conditions (Xu et al, 2020b). NCEP (National Centers for Environmental Prediction) reanalysis horizontal wind in BCN (not shown) reveals strong winds (~18 m s -1 ) at the beginning of the episode and much more stagnant conditions (<5 m s -1 ) towards the end of the episode.…”
mentioning
confidence: 97%
“…Secondary aerosol formation is enhanced in stagnant (low winds) and high humidity conditions (Xu et al, 2020b s -1 ) at the beginning of the episode and much more stagnant conditions (<5 m s -1 ) towards the end of the episode. All in all, such conditions might have favored the transfer of small dust particles to larger sizes and the growth of coarse-mode particles along the transport.…”
mentioning
confidence: 98%
“…In particular, when the transport of mineral dust occurs over polluted regions anthropogenic inorganic acids can be absorbed by the dust surface forming hygroscopic salt compounds that coat the dust particles (Abdelkader et al, 2015;Athanasopoulou et al, 2016). Dust also favors the formation of secondary pollutants (Querol et al, 2019;Xu et al, 2020b).…”
mentioning
confidence: 99%